GUTS and Strings-GUTS (2000)
ABSTRACT: We look for a connection between string theories and Grand Unified Theories (GUTs), with the aim to look for new insights in the existing four dimensional string-GUT problems. We argue that the construction of consistent string-GUT models could require the use of non-canonical affine levels. We list the most common level values related to realistic GUTs.